MUTYH-associated polyposis (MAP), the syndrome implicating base excision repair in inherited predisposition to colorectal tumors - Venesio, Tiziana; Balsamo, Antonella; D'Agostino, Vito; Ranzani, Guglielmina N. (Frontiers in Oncology, 2012)
In 2002, Al-Tassan and co-workers described for the first time a recessive form of inherited polyposis associated with germline mutations of MUTYH, a gene encoding a base excision repair (BER) protein that counteracts the DNA damage induced by the oxidative stress. MUTYH-associated polyposis (MAP) is now a well-defined cancer susceptibility syndrome, showing peculiar molecular features that characterize disease progression. However, some aspects of MAP, including diagnostic criteria, genotype-phenotype correlations, pathogenicity of variants, as well as relationships between BER and other DNA repair pathways, are still poorly understood. A deeper knowledge of the MUTYH expression pattern is likely to refine our understanding of the protein role and, finally, to improve guidances for identifying and handling MAP patients.